Nilai-Nilai Humanis Dalam Komunitas Segawon (Seduluran Nek Gadah Perlu Mawon) Di Kabupaten Wonosobo - Ahmad Fatih; Deni Sutan Bahtiar; Robingun Suyud El Syam (CV. Multi Kreasi Media, 2022)
Happy is the need of every human being, so it is necessary to refresh so that humans can express their feelings, not be trapped in a rigid atmosphere so that values ​​as humans who have the right to be happy and appreciated can be realized. Through a field approach, the research results: that there are humanist values ​​in the Segawon community, namely brotherhood, kinship, solidarity, virtue, intimacy, dialogue, tolerance and tolerance. These values ​​support a harmonious atmosphere so that community members can be successful in life.